DOI: 10.11606/t.23.2013.tde-19122013-150534
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de diferentes materiais no selamento de lesões cariosas de sulcos e fóssulas sem cavitação clínica: um ensaio clínico, controlado e randomizado

Abstract: Ao Senhor Jesus Cristo, pois sem Ele, nada disso seria possível. Aos meus pais, Roberto Campos Sales da Silveira e Jane Silva da Silveira, meu muito obrigado pelo apoio e incentivo constantes e sempre presentes na minha vida. A minha família, no papel do meu noivo, Clauber Figueiredo Martins, meus irmãos, Ana Beatriz Silva da Silveira e Roberto Campos Sales da Silveira Segundo, e a minha avó, Rita Silva da Silveira, pelo cuidado e carinho que me deram o suporte de que tanto precisei. A minha orientadora, Profª… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…In all the studies, the caries lesion was arrested in 100% of the sealed teeth. Except in a study that presented 64.3% success rate in sealed lesions with glass ionomer sealant and 85.7% in lesions sealed with resin sealant [19]. In the present study the non-removal of the carious tissue did not present differences when compared to teeth restored with healthy dentin in relation to the infiltration of the methylene blue dye.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In all the studies, the caries lesion was arrested in 100% of the sealed teeth. Except in a study that presented 64.3% success rate in sealed lesions with glass ionomer sealant and 85.7% in lesions sealed with resin sealant [19]. In the present study the non-removal of the carious tissue did not present differences when compared to teeth restored with healthy dentin in relation to the infiltration of the methylene blue dye.…”
Section: Discussioncontrasting
confidence: 73%
“…The quantitative evaluation, carried out by means of a comparison between the coefficients of demographic density, showed an increase of the density coefficients in Gres and in the Gciv a stability of the coefficients. Thus, it can be concluded that, under the conditions of this study, the use of pit and fissure sealants was effective in the treatment of carious lesions [19].…”
Section: Conclusãomentioning
confidence: 56%
“…Radiographs were used from non-cavitated occlusal caries lesions obtained in a previous study by Silveira 6 . Twenty-eight radiographs obtained York, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Radiographs were taken with a standardized angle of incidence of the X-ray beam and at a standardized distance between the appliance and the tooth film, which was determined using an acrylic resin bite guide. 6 Therefore, the radiographs could be repeated with the same distance from the film source (40 cm) and the same vertical and horizontal angulations. Two types of radiographic films and the same X-ray device were used for each patient.…”
Section: Methodsmentioning
confidence: 99%